MENTAL HEALTH, EMBODIED RESILIENCE, AND ATHLETIC LONGEVITY: A CASE STUDY OF A VETERAN COMBAT ATHLETE’S PSYCHOLOGICAL ADAPTATION UNDER STRESS, CHANGE, AND FORCED MIGRATION - Olha Cherepiekhina; Vladymyr Rudchenko (International Journal of Innovative Technologies in Social Science, 2025)
This article explores the role of sport as a system of psychological support and embodied resilience in the context of stress, change, and forced migration. Using a qualitative case study of Volodymyr Rudchenko, a veteran judo and sambo athlete, we examine how structured physical activity, social integration through sport, and modern health technologies contribute to mental health and athletic longevity among displaced individuals over 40 years of age. The study highlights the mechanisms by which sport serves as a critical tool for maintaining psychological stability, rebuilding personal identity, and fostering community belonging after major life disruptions. Findings suggest that the combination of cognitive-behavioral strategies, embodiment practices, and systematic health monitoring enables veteran athletes to successfully adapt to new environments and sustain competitive performance. The article proposes the "Embodied Resilience Model for Displaced Athletes" as a conceptual framework for developing targeted support programs in the fields of public health, social adaptation, and veteran athlete welfare.